Gastric duplication cyst: A rare congenital anomaly (Indian Journal of Case Reports, 2018)
Gastrointestinal (GI) duplication is defined as a spherical structure, with a muscular coat lined by a mucous membrane in the alimentary tract is a rare congenital anomaly. In this report, we present a case of a 14-year-old male child with complaints of epigastric pain for 1 month. Computed tomography scan of the abdomen was suggestive of two cystic lesions in the stomach. Exploratory laparotomy was performed with excision of cysts. Histopathology of both cysts was suggestive of gastric duplication cyst.